2020
DOI: 10.1007/s00787-020-01478-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring obsessive–compulsive disorder and autism spectrum disorder in young people: prevalence, clinical characteristics and outcomes

Abstract: Obsessive-compulsive disorder (OCD) and autism spectrum disorders (ASD) commonly co-occur and are considered challenging to manage when they co-occur in youth. However, clinical characteristics and prognosis of this group remain poorly understood. This study examined the prevalence, clinical correlates and outcomes of paediatric OCD co-occurring with ASD (OCD + ASD) in a large clinical cohort. Data were extracted from electronic clinical records of young people aged 4-17 years who had attended a mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…For example, a widely held clinical view is that individuals with co-occurring OCD and ASD tend to require more OCD treatment sessions over a longer period of time to make meaningful gains, compared to those without ASD. Consistent with this, previous research has shown that young people with OCD + ASD are engaged with clinical services for significantly longer than those without ASD [7]. However, to date, there is no empirical data to support this view, and it remains unclear whether extending treatment confers an added benefit.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…For example, a widely held clinical view is that individuals with co-occurring OCD and ASD tend to require more OCD treatment sessions over a longer period of time to make meaningful gains, compared to those without ASD. Consistent with this, previous research has shown that young people with OCD + ASD are engaged with clinical services for significantly longer than those without ASD [7]. However, to date, there is no empirical data to support this view, and it remains unclear whether extending treatment confers an added benefit.…”
Section: Introductionmentioning
confidence: 70%
“…OCD is particularly common among young people with autism spectrum disorder (ASD); it is estimated that up to 37% of those with ASD also experience OCD [5,6]. Young people with both OCD and ASD (OCD + ASD) have higher levels of functional impairment, utilise more mental health services, and have poorer outcomes following multimodal treatment for OCD, compared to those with OCD who do not have a diagnosis of ASD [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is described in the current literature that around 25% of people with OCD are also diagnosed with ASD. 2 Of those with a diagnosis of ASD, approximately 5% also have an OCD diagnosis. 2 It is likely that OCD is underdiagnosed in ASD because ASD associated problems outshine OCD symptoms, or since OCD symptoms overlap with ASD phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…2 Of those with a diagnosis of ASD, approximately 5% also have an OCD diagnosis. 2 It is likely that OCD is underdiagnosed in ASD because ASD associated problems outshine OCD symptoms, or since OCD symptoms overlap with ASD phenomena. Also, there may be an erroneous over--diagnosis of OCD in individuals with ASD if the nuclear symptoms of the last, such as resistance to change, highly restricted interests/routines and ritualized patterns of behavior, are misunderstood and erroneously considered as obsessions or compulsions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation